THE READING COMPREHENSION: THE USE OF START SIMPLE STORIES EXTENSIVE READING METHOD AT SMAN 5 PINRANG - Fahrul Fauzi; Muh Firmansyah JN (STKIP Darud Da'wah Wal Irsyad Pinrang, 2026)
Reading comprehension remains a fundamental skill in English learning because it determines students' ability to obtain information, identify main ideas, and interpret written texts. This study aimed to examine whether the Start Simple Stories Extensive Reading (SSS ER) method could improve the reading comprehension of tenth-grade students at SMAN 5 Pinrang. The study employed a quantitative pre-experimental design with a one-group pre-test and post-test model. The sample consisted of 29 students from class X.4 selected through purposive sampling because the class needed instructional support in reading comprehension. Data were collected through multiple-choice reading tests administered before and after the treatment. The findings showed a clear increase in students' achievement. The mean score increased from 45.86 in the pre-test to 82.07 in the post-test, while the standard deviation decreased from 14.52 to 7.74. The t-test value was 14.48, which was higher than the t-table value of 1.701. These results indicate that SSS ER was effective in improving students' reading comprehension. The method also encouraged students to read easier and more interesting texts independently without relying heavily on dictionaries.